1992
DOI: 10.3171/jns.1992.77.3.0379
|View full text |Cite
|
Sign up to set email alerts
|

Oblique sagittal magnetic resonance imaging visualizing vascular compression of the trigeminal or facial nerve

Abstract: An oblique sagittal magnetic resonance (MR) imaging method was developed to provide better visualization of vascular compression of nerves. The MR images of 12 patients with trigeminal neuralgia and 24 with hemifacial spasm were analyzed. The oblique sagittal views were obtained along the nerve identified by the axial view at an angle of 105 degrees between the line along the dorsal brain stem and the line along the margin of the pontomedullary junction (in patients with hemifacial spasm) or by the midsagittal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…Recently, MRT accurately and non-invasively assesses the neurovascular relations and neurovascular compression in the posterior fossa. 6,7 Clinical studies using MRT have suggested that the neurovascular compression may cause hypertension has been reported. 8,9,13 The frequency of neurovascular compression of the RVLM has been found to be high in German, 9 Italian 14 and Japanese 8,9 patients with essential hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, MRT accurately and non-invasively assesses the neurovascular relations and neurovascular compression in the posterior fossa. 6,7 Clinical studies using MRT have suggested that the neurovascular compression may cause hypertension has been reported. 8,9,13 The frequency of neurovascular compression of the RVLM has been found to be high in German, 9 Italian 14 and Japanese 8,9 patients with essential hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…3 Neurovascular compression of the RVLM has been proposed as a cause of essential hypertension in a surgical case, 4 an angiographic study, 5 and more recent magnetic resonance tomography (MRT) studies. [6][7][8][9] Nagashi et al 10 have suggested that a large portion of cases of essential hypertension can be explained by neurovascular compression. However, there has been no clinical study of the mechanism of the neurovascular compression-induced increase in blood pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Du et al (1) reported that the relationship between nerves and vessels is in some cases difficult to evaluate by means of transversly orientated 3D FISP imaging; the use of the MPR algorithm or oblique sagittal orientation might well improve the precision of evaluation (10,11). Our 3D MPR studies provided additional information such as the direction of compression and the course ofthe compressive vessel.…”
Section: Discussionmentioning
confidence: 78%
“…The usefulness of neuradiological methods such as computed tomography and MRI are still controversial. MRI sensivity and specificity to diagnose VBD are unknown 15 . Some authors emphasized that good results depend on the correct MRI projection (oblique sagittal) and the appropriate gradient echo sequences.…”
Section: Discussionmentioning
confidence: 99%